Flipbook as Innovation of Digital Learning Media: Preparing Education for Facing and Facilitating 21st Century Learning - Roemintoyo, Roemintoyo; Budiarto, Mochamad Kamil (Universitas Pendidikan Ganesha, 2021)
Various competencies that students need to master in an effort to strengthen competitiveness, especially in the field of human resources in the 21st century. Learning media integrated with technology is one of the important learning resources to support the learning process. The lack of innovation in the use of learning media that is integrated with technology makes it less optimal for the achievement of learning objectives and mastery of competencies by students. This study aims to identify the need for opportunities for developing instructional media that are integrated with flipbook-based technology in the hope that it can increase students' opportunities in improving scientific literacy skills. This research is a qualitative research with a survey method. Data collection techniques using observations and needs analysis questionnaires. The quantitative data from the questionnaire were then analyzed using quantitative descriptive techniques using percentages that were displayed in a table. The research subjects took senior high school students in grades one and two, with a total of 70 students. The results of this study indicate that 35.7% of students stated that teachers still use Microsoft Powerpoint media and 27.1% of printed teaching materials. The results also showed that students had positive perceptions of the opportunities for developing and utilizing flipbooks as a medium for digital learning. Through the results of this research, it can become the basis for educators in developing and implementing flipbook-based digital learning media to facilitate the learning process.